2020
DOI: 10.1177/1758835920915302
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vimentin, anti-TUFM, anti-NAP1L1 and anti-DPYSL2 nanobodies display cytotoxic effect and reduce glioblastoma cell migration

Abstract: Background: Glioblastoma is a particularly common and very aggressive primary brain tumour. One of the main causes of therapy failure is the presence of glioblastoma stem cells that are resistant to chemotherapy and radiotherapy, and that have the potential to form new tumours. This study focuses on validation of eight novel antigens, TRIM28, nucleolin, vimentin, nucleosome assembly protein 1-like 1 (NAP1L1), mitochondrial translation elongation factor (EF-TU) (TUFM), dihydropyrimidinase-related protein 2 (DPY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 88 publications
(144 reference statements)
1
43
0
Order By: Relevance
“…FREM2 and SPRY1 have been proposed as potential new markers of GBM, and have been demonstrated to be significantly upregulated in GBM at the mRNA and/or protein level in GBM cell lines and GBM tissues compared to references (astrocytes or reference non-malignant brain tissue) [6,19]. Furthermore, VIM, NCL, and NAP1L1 were significantly overexpressed in GBM tissues and/or cells compared to the reference [20,21]. Some of the proposed genes have also been implicated in other cancers, for example gastric cancer (vimentin) [37], large B-cell lymphoma (nucleolin) [38], and pancreatic cancer (NAP1L1) [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FREM2 and SPRY1 have been proposed as potential new markers of GBM, and have been demonstrated to be significantly upregulated in GBM at the mRNA and/or protein level in GBM cell lines and GBM tissues compared to references (astrocytes or reference non-malignant brain tissue) [6,19]. Furthermore, VIM, NCL, and NAP1L1 were significantly overexpressed in GBM tissues and/or cells compared to the reference [20,21]. Some of the proposed genes have also been implicated in other cancers, for example gastric cancer (vimentin) [37], large B-cell lymphoma (nucleolin) [38], and pancreatic cancer (NAP1L1) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we investigated whether the target genes of the selected miRNAs-NAP1L1, FREM2, SPRY1, VIM, and NCL-that have been associated with GBM in our previous studies [6, [19][20][21] were also present in the sEVs of different cell types and showed any particular expression pattern in GBM-isolated sEVs compared to normal astrocyte cells. qPCR was used for analysis.…”
Section: Vimentin Gene Is Overexpressed In Sevs Originating From U251mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the results of the present study, which demonstrated that late apoptotic cells were increased in the TUFM-silenced GIST-T1 cell line, are consistent with the aforementioned research revealing inhibited mitochondrial autophagy and damaged mitochondrial scavenging in TUFM stable knockout mice and TUFM-silenced 293T cells. These changes lead to considerable mitochondrial disintegration factor release and increased apoptosis (40). TUFM silencing directly induces mitochondrial protein synthesis inhibition, membrane dysfunction and mitochondrial structural dysfunction, which eventually leads to mitochondrial damage or disintegration, which is an important contributor to tumor cell apoptosis (41).…”
Section: Discussionmentioning
confidence: 99%